Implementation of Safety Management of Selected Construction Companies in Manila - Carolino , Reynaldo C.; Bernabe , Guillermo O.; Bianes , Joseph Raniel (International Journal of Membrane Science and Technology, 2023)
In the 1980s, the safety management system (SMS) was created to reduce material waste and the risk of accidents and fatalities in the construction industry. With the correct SMS deployment, construction companies can reduce safety-related difficulties. This study assessed the current status of construction safety management intending to determine the level of implementation of selected construction companies with category AAA in Manila, Philippines. A survey was done to determine the SMS implementation level in terms of lack of control, basic cause, immediate cause, incident, and accident. The researcher used the quantitative method of research with the survey questionnaire as the main tool in gathering data. Architects, engineers, safety officers, and skilled workers were the respondents of the study. The gathered data were statistically treated with the use of Frequency, Percentage, Weighted Mean, Kruskal Wallis, Man Whitney U-test, and Spearman Rho Correlation. The overall results showed that the level of the selected construction companies in Manila is somewhat implemented. The results of this study are helpful to the industry as well because they can improve the understanding of SMS among industry professionals and aid in better SMS deployment at work.